Economia e cultura. Linee di possibile ricomposizione - Vitaletti, Giuseppe (Il sogno della farfalla, 2012)
The birth of economics as a science dates back to the 18th century, when this branch of knowledge distances itself from the moral sciences and in general from the humanities while remaining, however, strictly anchored to them. Proof of this is the fact that great authors like Smith, Ricardo and Marx, also made important contributions to the philosophical field. Smith’s work, in particular, greatly featured in this article, is considered the beginning of economic theory, as well as having played a pivotal role in Scottish Enlightenment, which was significantly different from the European one. From the second half of the 1800s, after Marx, a radical change becomes though evident. Economics begins to find a place among the mathematical and natural sciences since it starts basing itself more and more on the construction of abstract formal models founded on hypotheses detached from reality. There are, however, lines of resistance, which attempt to make reference to classical authors or criticize the new orientation. The contributions of De Viti de Marco, Einaudi, Hirsch, Leijonhuvfud and Sraffa on the subject are quoted. The “core” thesis of this article is that a revival of Smith’s approach, coupled with these stirrings of resistance, could provide us with a good basis for founding a correct political economy, capable in particular to face the big crisis that the Western world, and especially Europe, is experiencing. It is also important that new cultural reference points emerge, able to overcome the abstraction of Rationalism, Idealism and Freudism, which relates to the former two, and capable of providing a scientific analysis of human reality without falling into Positivism or Fideism, as the theory upheld by this magazine manages to do. Perhaps it is possible to draw parallels between such a theory and the work of some of the authors quoted.